Effect of Added Water, Holding Time, or Phytase Analysis Method on Phytase Stability and Pellet Quality - M. Saensukjaroenphon; C. E. Evans; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
The addition of water to the mixer prior to pelleting is sometimes necessary to reach the target moisture content at the end of the conditioning process. However, there are limited data to demonstrate the impact of water addition in the mixer on phytase stability during the pelleting process. In addition, the variation of phytase analysis method may lead to incorrect or biased conclusions for research on industrial phytase stability. Therefore, the objective of this experiment was to determine the effect of water added in the mixer, feed holding time, and phytase analysis method on phytase stability and pellet quality. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of added water (0% or 1%), holding time (0 or 2 h), and phytase analysis method (ELISA or EN ISO), respectively. For the 0% added water treatment, a 210-lb basal feed and 0.03-lb phytase were mixed for 5 min. For the 1% added water treatments, a 208-lb basal feed and 0.03-lb phytase were mixed for 120 s followed by the addition of 2-lb water and then the mixture was mixed for 180 s wet mix time. The water was applied to dry feed in the mixer using a hand-held sprayer (Country Tuff model 26329, Sedalia, MO) with a flat spray tip nozzle (TeeJet model TP11006, Glendale Heights, IL). After the diets were mixed, treatments were immediately pelleted or held in a closed container for 2 h before pelleting. Treatments were steam conditioned at 185°F for approximately 30 s and pelleted using a pellet mill (California Pellet Mill Co. model Cl-5, Crawfordsville, IN). The pellet mill was equipped with a 0.16 × 0.87 in die. Samples were collected during discharge of the mixer, after conditioning and after pelleting. The conditioned mash and pelleted samples were cooled for 10 min using an experimental counterflow cooler. There were 3 replicates per treatment. Data were analyzed using the GLIMMIX procedure of SAS. The results demonstrated that there was no evidence of three-way or two-way interactions among added water, holding time, and analysis method on phytase stability for mash samples, conditioned mash samples, and pellets. The added water and holding time did not impact phytase stability for mash samples, conditioned mash samples, and pellets. The ELISA method had greater (P= 0.004) phytase activity than the EN ISO method for the pellet samples. The phytase activity was similar between the two analytical methods for mash samples and conditioned mash samples. For pellet quality, there was no evidence of interaction between added water and holding time. Added water and holding time did not impact pellet durability index. Therefore, the stability of phytase produced by a strain ofTrichoderma reeseiwas not affected when feed was stored in a bin up to 2 h prior to pelleting. The added water in mash feed did not affect the degradation ofTrichoderma reeseiphytase when the feed moisture did not exceed 13%. Additionally, the ELISA or EN ISO method could be used in the laboratory to determineTrichoderma reeseiphytase stability. Increasing moisture content of mash feed by 0.6% did not improve pellet quality.
Keywords: phytase; pellet quality; phytase stability